2005
DOI: 10.1080/j.1440-1614.2005.01701.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Self-Reported Potentially Traumatizing Events, Psychoform and Somatoform Dissociation, and Absorption, in Two Non-Clinical Populations

Abstract: Objective: Some authors have suggested that the personality characteristic 'fantasy proneness' may mediate the correlation between reported potentially traumatizing events and dissociative symptoms. Other authors question the reported magnitude of this correlation in non-clinical samples because these are usually derived from student samples and may therefore suffer from a restriction of range. The primary aim of this study is to assess the relationship between a self-report measure of traumatisation and psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 33 publications
3
23
0
Order By: Relevance
“…Our results also indicated that high levels of fantasy proneness and dissociation were related to higher scores on most of the clinical scales on the TSI, which is consistent with some previous research. For example, Naring and Nijenhuis (2005) found that individuals rated high on dissociation displayed these tendencies when reporting various traumatic events. Similarly, Titchenor et al (1996) reported levels of dissociation linked to greater PTSD symptom reporting.…”
Section: Discussionmentioning
confidence: 99%
“…Our results also indicated that high levels of fantasy proneness and dissociation were related to higher scores on most of the clinical scales on the TSI, which is consistent with some previous research. For example, Naring and Nijenhuis (2005) found that individuals rated high on dissociation displayed these tendencies when reporting various traumatic events. Similarly, Titchenor et al (1996) reported levels of dissociation linked to greater PTSD symptom reporting.…”
Section: Discussionmentioning
confidence: 99%
“…This is compatible with the notion of somatoform dissociation, a term coined by Nijenhuis (1999) to describe a disruption between the normal mental synthesis of ideas and functions, which can lead to presentations as negative symptoms (loss of function as e.g., anesthesia or paralysis) or positive symptoms (e.g., altered function as pain). Although the mental and physiological processes leading to dissociative symptoms are not completely understood, the association of dissociative symptoms with traumatizations is empirically well validated (Naring and Nijenhuis, 2005;Pribor et al, 1993;van der Kolk et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The original hypothesis, developed from Pierre Janet's work, claimed that dissociation is a defensive coping strategy for overwhelming traumatic events (Giesbrecht, Geraerts & Merckelbach, 2007;Martinez-Toboas & Bemal, 2000;Naring & Nijenhuis, 2005;van der Boom, van den Hout, & Huntjens, 2010). The other hypothesis links high fantasy proneness to dissociative tendencies, an association that suggests that, while fantasy proneness is integral to healthy psychological functioning, when it is extensive, vivid, and uncontrolled, it can decrease cognitive processing, increase dissociation, and bias trauma selfreports (Merkelbach, Horselenberg & Schmidt, 2002).…”
mentioning
confidence: 99%